Vitamin D Kinetics and Parathyroid Gland Function in Patients with Congenital Heart Disease. (4th July 2016) - Izumi, Gaku; Inai, Kei; Shimada, Eriko; Nakanishi, Toshio
Abstract: Objective: It has been recently reported that vitamin D deficiency may contribute to systemic illnesses that accompany chronic heart failure. These reports also suggest the serum levels of parathormone, which activates vitamin D in the liver, can be a useful marker of heart failure. This study was designed to evaluate the clinical implications of vitamin D and parathormone levels in patients with congenital heart diseases and chronic heart failure. Design: We measured 25‐hydroxyvitamin D and parathormone serum levels in 103 adult patients with congenital heart diseases (age range 20–89 years). Of 103 patients, 54 were in New York Heart Association functional classes II or III. Their clinical data regarding cardiothoracic ratio, fractional shortening of the systemic ventricle, brain natriuretic peptide plasma levels, and pulse oximetry were also evaluated. Results: Of 54 patients with chronic heart failure, 50 (93%) exhibited vitamin D deficiency (25‐hydroxyvitamin D serum levels <50 nmol/L) or elevation of parathormone (serum levels >65 pg/mL). These two parameters were inversely correlated. In multivariate analyses including age, gender, 25‐hydroxyvitamin D, parathormone, pulse oximetry, cardiothoracic ratio, calcium, phosphorus, glomerular filtration rate, albumin, creatine kinase, end‐diastolic diameter and fractional shortening of the systemic ventricle, and ratio of early diastolic transmitral flow velocity to mitral annular velosity, only the parathormone serum levels ( P  < .01) remained independently associated with brain natriuretic peptide plasma levels. Moreover, in multivariate analyses including the same variables minus parathormone serum levels, both pulse oximetry ( P  < .01) and glomerular filtration rate ( P  < .01) remained independently associated with parathormone levels. Conclusions: Vitamin D deficiency and secondary hyperparathyroidism are common in patients with congenital heart diseases and heart failure. Serum parathormone and 25‐hydroxyvitamin D levels correlated with several clinical heart failure markers, suggesting that vitamin D deficiency may deteriorate heart function in congenital heart disease patients.